EEC and the Third World : a survey. - Overseas Development Institute (London, England); Institute of Development Studies (Brighton, England) (New York : Holmes & Meier, 1981)
The survey aims to pull together the many strands of EEC policies and actions that affect the third world. It brings to this analysis the weight of research being undertaken in European centres and elsewhere, and publishes at a time when particular interest has been generated in the relationship between North and South by the report of the 'Brandt' Commission
Published simultaneously in Great Britain: London : Hodder and Stoughton.
Includes index
osc 09/11/2018
Loans
Keywords: International economic relations; European Economic Community countries; Developing countries; Developing countries; Europe